Performance, emission and combustion characteristics of a multicylinder common rail direct injection diesel engine fuelled with ethanol-acid oil methyl ester-diesel blends. Issue 1 (2nd January 2020) - Rajesh, S.; Banpurmath, N. R.; Kulkarni, B. M.; Kumarappa, S.
ABSTRACT: In the present work biodiesel was used as an emulsifier for diesel and ethanol mixtures and used for diesel engine applications. The biodiesel was produced from acid oil, a waste by-product of vegetable oil refineries. The fatty acid methyl ester mixture, called acid oil methyl ester (AOME), was blended with diesel and ethanol. Characterization of these ethanol-biodiesel-diesel (EBD) blends was done to ascertain their suitability for common rail direct injection (CRDI) engines. The objective of the present work is to determine the optimal use of EBD blends. The selected blends were tested in a four-cylinder CRDI engine for different loads and at engine speeds of 1200, 1500 and 1800 rpm. Performance, emission and combustion characteristics of these blends ware then compared with standard diesel fuel. The studies indicate decreased brake thermal efficiency and increased carbon monoxide, hydrocarbon and smoke emissions as alcohol concentration in the blends increased while NOx emissions were significantly reduced. As engine speeds increased from 1200 to 1800 rpm, brake thermal efficiency increased, carbon monoxide, hydrocarbon and smoke emissions were reduced and NOx emissions increased significantly. Knocking was observed for engine speeds beyond 1800 rpm.